Actual and Model-Predicted Growth of Sponges—With a Bioenergetic Comparison to Other Filter-Feeders - Hans Ulrik Riisgård; Poul S. Larsen (Journal of Marine Science and Engineering, 2022)
Sponges are one of the earliest-evolved and simplest groups of animals, but they share basic characteristics with more advanced and later-evolved filter-feeding invertebrates, such as mussels. Sponges are abundant in many coastal regions where they filter large amounts of water for food particles and thus play an important ecological role. Therefore, a better understanding of the bioenergetics and growth of sponges compared to other filter-feeders is important. While the filtration (pumping) rates of many sponge species have been measured as a function of their size, little is known about their rate of growth. Here, we use a bioenergetic growth model for demosponges, based on the energy budget and observations of filtration (F) and respiration rates (R). Because F versus dry weight (W) can be expressed as F = a1Wb1 and the maintenance respiratory rate can be expressed as Rm = a2Wb2, we show that if b1~ b2 the growth rate can be expressed as: G = aWb1, and, consequently, the weight-specific growth rate is µ = G/W = aWb1−1 = aWb where the constant a depends on ambient sponge-available food particles (free-living bacteria and phytoplankton with diameter < ostia diameter). Because the exponent b1 is close to 1, then b ~ 0, which implies µ = a and thus exponential growth as confirmed in field growth studies. Exponential growth in sponges and in at least some bryozoans is probably unique among filter-feeding invertebrates. Finally, we show that the F/R-ratio and the derived oxygen extraction efficiency in these sponges are similar to other filter-feeding invertebrates, thus reflecting a comparable adaptation to feeding on a thin suspension of bacteria and phytoplankton.